Atypical clinical manifestations and genotype-phenotype correlations of neurofibromatosis type 1 - R. N. Mustafin (Сибирский онкологический журнал, 2022)
Purpose of the study: Analysis of available data on geno-phenotypic correlations and atypical forms of neurofibromatosis type 1. Material and methods. We searched for relevant sources in the Scopus, Web of Science, PubMed systems, including publications from May 1993 to October 2021. Of the 318 studies  we identified, 59 were used to write a systematic review. Results. We found studies describing atypical forms of neurofibromatosis type 1 with an erased course without manifestation of a tumor syndrome, which are caused by specific mutations in the NF1 gene (causing substitutions of amino acids in neurofibromin: p.Arg1038, p.Met1149, p.Arg1809, or deletion of amino acids: p.Met990del, p.Met992del). NF1 patients with microdeletions are characterized by more severe disease symptoms (more often facial dysmorphism, skeletal and cardiovascular abnormalities, learning difficulties, and symptomatic spinal neurofibromas). mutations of splicing sites and extended deletions of the NF1 gene are associated with early manifestation of tumors, mutations at the 5’-end of the gene, causing a shortening of the protein product, are associated with optic nerve gliomas. the mutation c.3721C>T (p.R1241*) correlated with structural brain damage, and c.6855C>A (p.Y2285*)  with  endocrine  disorders. the  manifestations  of  NF1,  similar  to  lipomatosis  and Jaffe-Campanacci syndrome, not associated with a specific type of mutation are described. Conclusion.  In spite of pronounced clinical variability of the disease, even among members of the same family, several studies have described genotype-phenotype correlations. Therefore, the role of modifier genes and epigenetic factors in the pathogenesis of NF1 is assumed, since the neurofibromin protein has a complex structure with several functional domains. It has been shown that the severity of the tumor syndrome is influenced by the methylation characteristics of NF1 gene and adjacent areas. in addition, NF1 gene is associated with a variety of microRNAs. therefore, targeted therapy aimed at specific non-coding RNAs to restore normal expression of NF1 gene can become a promising treatment for NF1.